1983
DOI: 10.1128/jcm.17.4.576-581.1983
|View full text |Cite
|
Sign up to set email alerts
|

Agglutination of Naegleria fowleri and Naegleria gruberi by antibodies in human serum

Abstract: The capability of serum samples from 423 human subjects to agglutinate rounded cells of Naegleria fowleri nN68 was assessed. Sera from the umbilical cords of seven infants failed to agglutinate N. fowleri cells. The median agglutination titer was 1:4 for sera from children through age 4 years, 1:8 for sera from juveniles 5 to 15 years of age, and 1:16 for sera from subjects 15 to 30 years old. The agglutination titers of sera from older adults decreased to a median of 1:8 for the 40to 60-year-old age group and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…Cursons et al (7,8) proposed that unwitting exposure of humans to antigenically related nonpathogenic amoebae may prime the immune system to resist an infection by N. fowleri. Because the humoral antibody response does not correlate with protective immunity in mice, we propose that the presence of circulating antibodies to N. fowleri in humans indicates prior exposure to corresponding antigens but does not indicate the status of host resistance to this protozoan parasite (25,26). Holbrook et al (14) observed that the role of complement in innate immunity to N. fowleri infections deserves further study.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Cursons et al (7,8) proposed that unwitting exposure of humans to antigenically related nonpathogenic amoebae may prime the immune system to resist an infection by N. fowleri. Because the humoral antibody response does not correlate with protective immunity in mice, we propose that the presence of circulating antibodies to N. fowleri in humans indicates prior exposure to corresponding antigens but does not indicate the status of host resistance to this protozoan parasite (25,26). Holbrook et al (14) observed that the role of complement in innate immunity to N. fowleri infections deserves further study.…”
Section: Discussionmentioning
confidence: 83%
“…This difference, in part, reflects differences in the agglutination assays used. We have found that N. fowleri cells rounded by chilling and suspended in minimum essential medium agglutinate more effectively and reproducibly than do living amoebae in Page saline (26). In fact, failure to detect agglutinating activity for N. gruberi in human serum (25) has been attributed to the use of live amoeboid cells rather than rounded cells in the assay.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The humoral immune response to Naegleria has been studied in humans and experimental animals. Serum samples from healthy individuals from the United States (Reilly et al, 1983a;, New Zealand (Cursons et al, 1977(Cursons et al, , 1980a, and the Czech Republic (Cerva, 1989) have been examined for antibodies to N. fowleri. Although the antibody titers recorded have differed from study to study, almost all human sera from healthy individuals have been found to be positive for N. fowleri, indicating that exposure to the ameba is common.…”
Section: Humoral Immunitymentioning
confidence: 99%
“…Immunity to pathogenic free-living amoebae requires the stimulation of an antibody response which is important in opsonizing amoebae for neutrophil-mediated killing (8,13,18,36). Cell-mediated immunity has also been previously described for N. fowleri (6), and this response may act to produce cytokines, which augment the neutrophil response against the amoebae (8,13).…”
Section: Discussionmentioning
confidence: 97%